A programming framework for people as a service - Bandera García, David; Perez-Vereda, Alejandro; Canal-Velasco, José Carlos; Pimentel-Sánchez, Ernesto (My University, 2019)
The number of devices connected to the internet is constantly growing, which implies an increased complexity when interacting with so many heterogeneous devices. Automating this process is key to keep up with this growth. This People as a Service model works towards developing virtual profiles for every user in their own mobile devices and under their full control. These profiles allow to establish user preferences and predefined parameters, which are then applied by the devices they connect to. By integrating both the information in the virtual profiles and these devices, we can create a context in which to make smart decisions and apply them automatically, all of this in a decentralised way. In order to show our proposal in action, we have developed a treasure hunting game as a proof of concept to bring to the spotlight the utility of an environment with programmatically adapted devices.
Keywords: Internet; People as a Service; PeaaS; Beacons; Virtual Profile; Iot